Signature requirements and citizen initatives. Quasi-Experimental evidence from Germany. - Arnold, Felix; Freier, Ronny (My University, 2013)
Signature requirements are often used as hurdles to prevent overuse of public referenda. We evaluate the causal effect of lowering signature requirements on the number of observed citizen initiatives. Based on municipality-level data for Germany, we make use of legislative changes at specific population thresholds to build an identification strategy using a regression discontinuity design. We find that reducing the signature requirement by 1 percentage point increases the probability of observing an initiative by 8-10 percentage points. The results are robust to a variety of tests. Importantly, we go into great detail to rule out other potential confounders.
Keywords: Bürgerinitiative; Partizipation; Information; Kosten; Experiment; Untersuchung; Politikinstrument; Referendum; Datengrundlage; Schwellenwert; Beteiligung; Unterschrift; Rechtsgrundlage; Direkte Demokratie